Natural convection in a cross-fin heat sink. (5th March 2018) - Feng, Shangsheng; Shi, Meng; Yan, Hongbin; Sun, Shanyouming; Li, Feichen; Lu, Tian Jian
Highlights: A novel cross-fin heat sink was proposed for electronics cooling. Natural convection of the heat sink was experimentally and numerically examined. The overall heat transfer was enhanced by 11% than the plate-fin heat sink. Importantly, the geometrical complexity and material consumption was not increased. Abstract: A novel cross-fin heat sink consisting of a series of long fins and a series of perpendicularly arranged short fins was proposed to enhance natural convective heat transfer. The design principle of the cross-fin heat sink was based on overcoming internal thermal fluid-flow defects in a conventional plate-fin heat sink. The thermal performance of the proposed heat sink was compared with a reference plate-fin heat sink in horizontal orientation. A numerical model considering both natural convection and radiation heat transfer was developed to obtain thermal fluid-flow distributions and heat transfer coefficients of both the cross- and plate-fin heat sinks. Corresponding experiments were performed to validate the model predictions. It was demonstrated that, compared to the reference plate-fin heat sink, the cross-fin heat sink enhanced the overall (including natural convection and radiation) and convective (excluding radiation) heat transfer coefficients by 11% and 15%, respectively. Importantly, the enhancement was achieved without increasing the overall volume, material consumption, and too much extra cost. The proposed cross-fin heat sink provides a practical alternative to the widely adopted plate-fin heat sinks.